Regulation (EC) No 864/2007 Of The European Parliament And Of The Council of 11 July 2007 : on the law applicable to non-contractual obligations (Rome II) / The European Parliament, The Council Of The European Union - The European Parliament
These measuresare to include those promoting the compatibility of therules applicable in the Member States concerning the conflict of laws and of jurisdiction.